PENGARUH AKTIVA TAK BERUJUD TERHADAP KINERJA KEUANGAN DAN KEBIJAKAN KEUANGAN SERTA DAMPAKNYA PADA NILAI PERUSAHAAN (Studi Pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi di Bursa Efek Indonesia Periode 2013-2015) - SUYAMTO SUYAMTO (JURNAL WIDYA GANECWARA, 2017)
The purpose of this study are as follows: (1) Testing the influence of intangible assets (intav) on the value manufacturing companiesÂ  of consumer goods sector in Indonesia Stock Exchange. (2) Examine the effect of financial performance mediation (roa) on the influence of intangible assets on firm value. (3) Examine the effect of financial policy mediation (der) on the influence of intangible assets on firm value. This research was conducted on manufacturing companies listed in Indonesia Stock Exchange period 2013-2015. The population in this study are all companies manufacturing of consumer goods sector totaling 43 companies. Then take 29 sample of companies with purposive random sampling method. The results of the study found that there is a positive and significant influence of intangible assets to the value of the firm. There is an effect of financial policy mediation on the influence of intangible assets on firm value. The effect of financial policy mediation effect on intangible assets is partial. This means that the intangible assets directly or indirectly influence through the financial policy to the value of the firm. There is an effect of financial performance mediation on the influence of intangible assets on firm value. The effect of financial performance mediation effect on intangible assets is full mediation. This means that intangible assets will improve financial performance first, then financial performance will increase the value of the firm.